Cation-Exchange Synthesis of Lead Bismuth Sulfide Quantum Dots and Nanorods for Thermoelectric Applications - Baek, Seungmin; Cho, Soyoung; Kwon, Hyo Geun; Heo, Seung Hwae; Son, Jae Sung; Kim, Sang Wook (Chemistry of Materials, 2021)
Cation-exchange-induced phase transformations have recently been employed for the synthesis of a variety of nanomaterials. In this study, we induced a cation-exchange reaction by adding Bi-oleate to PbS quantum dots (QDs) and synthesized uniform Pb1-xBixSy QDs and nanorods (NRs) with a diameter of approximately 3 nm and length of 40 nm (aspect ratio 1:5), respectively. Colloidal QDs are promising materials for thermoelectric applications owing to their simple production process, easy dimensional control, low thermal conductivity, and high Seebeck coefficient. We studied the thermoelectric properties of Pb1-xBixSy QDs and NRs synthesized through cation exchange. The Pb1-xBixSy NRs exhibited high values of the Seebeck coefficient (-181.31 μV/K at 450 K) and power factor (3.14 μW/cm·K2 at 650 K), and the electrical conductivity dramatically increased from 0.91 to 14.88 S/cm with an increase in temperature.
Keywords: Cation exchange reactions; Dimensional control; Electrical conductivity; Induced phase transformation; Low thermal conductivity; Production process; Thermoelectric application; Thermoelectric properties